Assessment of SLE activity for acute clinical decision-making: use of a colour-coded threat-level approach for the non-rheumatologist - Cindy Flower (Lupus Science and Medicine)
Systemic lupus erythematosus (SLE) activity indices are widely applied in academic centres and for research protocols but are often not part of usual care in busy under-resourced clinical settings especially where non-rheumatologists are involved in SLE management. We developed a simplified activity index based on the established knowledge and experience of SLE in our hospital and further applied a treatment guideline to assist in acute clinical decision-making. The index is colour-coded for easy reference and categorizes clinical complications in order of the severity of the threat they pose to the patient. An index such as this can be modified to have wider application and relevance in other countries with reduced access to specialist care.